Better library and learning space : projects, trends and ideas - Watson, Les (London : Facet Publishing, 2013)
What are the most important things a 21st-century library should do with its space? Each chapter in this cutting-edge text addresses this critical question, capturing the insights and practical ideas of leading international librarians, educators and designers to offer you a'creative resource bank' that will help to transform your library and learning spaces. This is an innovative and practical toolkit introducing concepts, drawing together opinions and encouraging new ways of thinking about learning spaces in the future. It explores topics that include: the threat of change, including new models of learning and the revolution in technology; the role of the library, looking at new sustainable and creative library models; and, the power of space, exploring its effects on identity, psychology and behaviour. This is a must-have text for those involved in designing and developing library and learning spaces, from library and university management to designers and architects.
Includes bibliographical references and index.
Keywords: Libraries -- Space utilization; Library buildings -- Design and construction; Library planning